2006
DOI: 10.2503/hrj.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Varietal Variations in Pecan (Carya illinoensis Koch) Cultivars for Extending a Business Period of Tourism Farm in Autumn

Abstract: Pecans belonging to the same group as Japanese chestnut would be advantageous trees to extend the business cycle of tourism farming of chestnut trees in the autumn season. We investigated the flowering period of male and female flowers in twenty-five cultivars, and the harvest period and fruit quality in sixteen cultivars. It was observed that the female flower bloomed earlier than the male flower in most cultivars. However, there was an overlapping period of several days during the blooming of male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Only Pawnee variety represents poor kernel % especially in the 2 nd season as it recorded (42.36 %) comparing to the other varieties. These results are in agreement with those obtained by (Herrera, 1985;Yao et al, 2004;Thompson, 2005 andMaeda, 2006) they demonstrated that, some factors have to be taken into consideration when selecting a variety as regular production capacity, tree growth, branching properties, nut size and quality, kernel percentage, maturity and pollination characteristics. One of the most important characteristics of pecan fruit evaluation should be nut filling which give an idea of the edible part of the fruit and an indication for the nutritional status of the tree.…”
Section: Fruit Quality Characteristicssupporting
confidence: 91%
“…Only Pawnee variety represents poor kernel % especially in the 2 nd season as it recorded (42.36 %) comparing to the other varieties. These results are in agreement with those obtained by (Herrera, 1985;Yao et al, 2004;Thompson, 2005 andMaeda, 2006) they demonstrated that, some factors have to be taken into consideration when selecting a variety as regular production capacity, tree growth, branching properties, nut size and quality, kernel percentage, maturity and pollination characteristics. One of the most important characteristics of pecan fruit evaluation should be nut filling which give an idea of the edible part of the fruit and an indication for the nutritional status of the tree.…”
Section: Fruit Quality Characteristicssupporting
confidence: 91%